2005
DOI: 10.1083/jcb.200507106
|View full text |Cite
|
Sign up to set email alerts
|

p53 functions as a negative regulator of osteoblastogenesis, osteoblast-dependent osteoclastogenesis, and bone remodeling

Abstract: p53 is a well known tumor suppressor. We show that p53 also regulates osteoblast differentiation, bone formation, and osteoblast-dependent osteoclast differentiation. Indeed, p53 − / − mice display a high bone mass phenotype, and p53 − / − osteoblasts show accelerated differentiation, secondary to an increase in expression of the osteoblast differentiation factor osterix, as a result. Reporter assays indicate that p53 represses osterix transcription by the minimal promoter in a DNA-binding–independent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
225
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(248 citation statements)
references
References 52 publications
23
225
0
Order By: Relevance
“…Thus, OSM could affect bone formation not only by inducing differentiation but also by sensitizing proliferating osteoblasts to cell death. Whether p53 and STAT5 are implicated in this OSM-induced differentiation of osteoblasts deserves further investigations but recent in vivo studies with p53 knockout mice indicated that p53 inhibits osteoblast differentiation, bone development and neoplasia (Lengner et al, 2006;Wang et al, 2006). Similarly, STAT5ab À/À mice, although smaller than their wild-type littermates, have an increased number of trabecular osteoblasts and bone formation (Sims et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, OSM could affect bone formation not only by inducing differentiation but also by sensitizing proliferating osteoblasts to cell death. Whether p53 and STAT5 are implicated in this OSM-induced differentiation of osteoblasts deserves further investigations but recent in vivo studies with p53 knockout mice indicated that p53 inhibits osteoblast differentiation, bone development and neoplasia (Lengner et al, 2006;Wang et al, 2006). Similarly, STAT5ab À/À mice, although smaller than their wild-type littermates, have an increased number of trabecular osteoblasts and bone formation (Sims et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Atm − / − , p53 − / − , Smad1 − / − MEFs were prepared as previously described 30 . Atm − / − , p53 − / − , and Balb/c nude mice were bred and used, following the guidelines of the Institute of Molecular and Cell Biology, with protocols approved by Animal Care and Use Committee, Singapore.…”
Section: Methodsmentioning
confidence: 99%
“…These include the tumor suppressor p53, which decreases OSX levels through an unknown mechanism (Wang et al 2006), and NFATC1, a calcium-sensitive transcription factor that stimulates osteoblast differentiation by enhancing OSX transcriptional activity (Koga et al 2005;Winslow et al 2006).…”
Section: Other Transcription Factorsmentioning
confidence: 99%